Colonic catabolism of ellagitannins, ellagic acid, and raspberry anthocyanins: In vivo and in vitro studies - González-Barrio, R.; Edwards, Christine; Crozier, A. (2011)
Red raspberries contain principally anthocyanins and ellagitannins. After ingestion of raspberries by humans, trace levels of anthocyanins, absorbed in the upper gastrointestinal tract, are excreted in urine in amounts corresponding to <0.1% of intake. Urine also contains urolithin-O-glucuronides derived from colonic metabolism of the ellagitannins. Raspberry feedings with ileostomists show that substantial amounts of the anthocyanin and ellagitannin intake are excreted in ileal fluid. In subjects with an intact functioning colon, these compounds would pass to the large intestine. The aim of this study was to identify raspberry-derived phenolic acid catabolites that form in the colon and those that are subsequently excreted in urine. In vitro anaerobic incubation of ellagitannins with fecal suspensions demonstrated conversion to ellagic acid and several urolithins. Fecal suspensions converted 80% of added ellagic acid to urolithins. In vivo, urolithins are excreted in urine as O-glucuronides, not aglycones, indicating that the colonic microflora convert ellagitannins to urolithins, whereas glucuronidation occurs in the wall of the large intestine and/or postabsorption in the liver. Unlike ellagitannins, raspberry anthocyanins were converted in vitro to phenolic acids by anaerobic fecal suspensions. Urinary excretion of phenolic acids after ingestion of raspberries indicates that after formation in the colon some phenolic acids undergo phase II metabolism, resulting in the formation of products that do not accumulate when anthocyanins are degraded in fecal suspensions. There is a growing realization that colonic catabolites such as phenolic acids and urolithins may have important roles in the protective effects of a fruit- and vegetable-rich diet.